Phenotypic Characterization of a Novel Virulence-Factor Deletion Strain of Burkholderia mallei That Provides Partial Protection against Inhalational Glanders in Mice - Bozue, Joel A.; Chaudhury, Sidhartha; Amemiya, Kei; Chua, Jennifer; Cote, Christopher K.; Toothman, Ronald G.; Dankmeyer, Jennifer L.; Klimko, Christopher P.; Wilhelmsen, Catherine L.; Raymond, Jolynn W.; Zavaljevski, Nela; Reifman, Jaques; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Burkholderia mallei (Bm) is a highly infectious intracellular pathogen classified as a category B biological agent by the Centers for Disease Control and Prevention. After respiratory exposure, Bm establishes itself within host macrophages before spreading into major organ systems, which can lead to chronic infection, sepsis, and death. Previously, we combined computational prediction of host-pathogen interactions with yeast two-hybrid experiments and identified novel virulence factor genes in Bm, including BMAA0553, BMAA0728 (tssN), and BMAA1865. In the present study, we used recombinant allelic exchange to construct deletion mutants of BMAA0553 and tssN (ΔBMAA0553 and ΔTssN, respectively) and showed that both deletions completely abrogated virulence at doses of >100 times the LD50 of the wild-type Bm strain. Analysis of ΔBMAA0553- and ΔTssN-infected mice showed starkly reduced bacterial dissemination relative to wild-type Bm, and subsequent in vitro experiments characterized pathogenic phenotypes with respect to intracellular growth, macrophage uptake and phagosomal escape, actin-based motility, and multinucleated giant cell formation. Based on observed in vitro and in vivo phenotypes, we explored the use of ΔTssN as a candidate live-attenuated vaccine. Mice immunized with aerosolized ΔTssN showed a 21-day survival rate of 67% after a high-dose aerosol challenge with the wild-type Bm ATCC 23344 strain, compared to a 0% survival rate for unvaccinated mice. However, analysis of histopathology and bacterial burden showed that while the surviving vaccinated mice were protected from acute infection, Bm was still able to establish a chronic infection. Vaccinated mice showed a modest IgG response, suggesting a limited potential of ΔTssN as a vaccine candidate, but also showed prolonged elevation of pro-inflammatory cytokines, underscoring the role of cellular and innate immunity in mitigating acute infection in inhalational glanders.